An Empirical Investigation of The Exchange Rate Pass-Through To Domestic Prices in Nigeria “Exchange Rate Pass-Through To Domestic Prices” - Iyoha, Faith Arekpetan (Archives of Business Research, 2018)
The sensitivity of prices to fluctuations in the nominal exchange rate of the Nigerias currency has become a prominent subject for business and policy makers. The persistent depreciation in exchange rate and high domestic prices currently above the policy target is the basis of this study. The study adopted secondary data of monthly frequency covering January-2000 to June-2017, to test the exchange rate pass-through to domestic prices in Nigeria while controlling for effects of other variables such as monetary aggregates and fuel prices. Impulse response functions and variance decomposition under the purview of Vector Auto-regressive (VAR) modelling approach are employed for the analyses. It finds that the exchange rate pass-through to domestic prices is complete six months after exchange rate shock. However money supply and fuel price effect are stronger than the exchange rate effect although the fuel price impact decay over time. Given the stronger impact of money supply on prices, the study concludes that inflation is a monetary phenomenon thereby giving credence to the current policy anchor on money supply as a policy tool to control inflation. It therefore recommends that policy makers should continue to pursue and maintain exchange rate stance that eases the depreciation pressure